On some species of Gyrophaenina Kraatz 1856 of Sri Lanka and India (Coleoptera: Staphylinidae: Aleocharinae: Homalotini) - Enushchenko, Ilya V.; Shavrin, Alexey V. (Zootaxa, 2021)
New taxonomic and diagnostic data for 17 species of Encephalus Kirby, 1832, Gyrophaena Mannerheim, 1830 and Phanerota Casey, 1906 of Sri Lanka and India are provided. Eight species are redescribed: G. (Gyrophaena) furcata (Motschulsky, 1858), G. (G.) indica Motschulsky, 1858, G. (G.) kashmirensis Bernhauer, 1923, G. (G.) livida Motschulsky, 1858, G. (G.) permutaria Schubert, 1906, G. (G.) sexualis Cameron, 1939, G. (G.) soror Bernhauer, 1923, and Ph. (Acanthophaena) appendiculata (Motschulsky, 1858). The following new synonymies are established: G. (G.) cognata Cameron, 1939 = G. setiensis Pace, 2006 syn.n., G. (G.) indica = G. granulifera Kraatz, 1859 syn.n., G. cicatricosa Motschulsky, 1858 syn.n., G. rigida Motschulsky, 1858 syn.n., G. nigrides Newton, 2017 (replacement name for G. nigra Motschulsky 1859) syn.n., G. trifida Motschulsky, 1859 syn.n., G. (G.) livida = G. curtula Motschulsky, 1859 syn.n., and G. (G.) tripartita Cameron, 1939 = G. annapurnensis Pace, 2006 syn.n. Lectotypes for G. (G.) furcata, G. (G.) indica, G. (G.) kashmirensis, G. (G.) livida, G. (G.) soror Bernhauer, 1923, Ph. (Acanthophaena) appendiculata and Ph. (A.) rufiventris (Cameron, 1920) comb.n. (from Gyrophaena) are designated. The habitus of all taxa, aedeagi and apical abdominal sclerites of all species of Gyrophaena and Phanerota are illustrated. Gyrophaena (G.) jumlicola Pace, 2006 is recorded from India for the first time.